DIETARY REPLACEMENT OF SOYBEAN MEAL BY TOASTED SUNFLOWER SEEDMEAL IN THE DIET OF Clarias gariepinus: EFFECT ON GROWTH, BODY COMPOSITION, DIGESTIBILITY, HAEMATOLOGY AND HISTOPATHOLOGY OF THE LIVER. - Jimoh, Wasiu Adeyemi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
Dietary replacement of soybean meal by toasted sunflower meal in Clarias gariepinus diet was investigated in a 56-day feeding trial using growth, body composition, digestibility, haematology and liver histology as indices of assessment. Sunflower seed meal was toasted at 2040C for 5, 10 and 15 minutes. Control diet consist of soybean meal which was replaced by differently toasted sunflower seed meal at a rate 15, 30 and 45% to produce nine 40% crude protein, 18kj/kg test diets. Triplicate groups of fish in 70-litre capacity aerated rectangular plastic tanks were assigned to each dietary treatment at a stocking rate of 15 fingerlings (4.97±0.42g average weight) per tank in a completely randomized design. Fish were fed to satiation. Data generated from the experiment were subjected to one-way analysis of variance. The results of the experiment revealed that up to 30% replacement level of the differently toasted sunflower had a statistically similar results with soybean-based control diets using growth, body composition, digestibility and haematology as indices. Liver histology however show that massive fatty infiltration recorded in the liver of fish fed TSF145 and TSF 345 and diffuse vacuolar degeneration of hepatocytes and kupffer cell hyperplasia observed in the liver of fish fed TSF245 and TSF330.